Preliminary examination of metabolic syndrome response to motivational interviewing for weight loss as compared to an attentional control and usual care in primary care for individuals with and without binge-eating disorder. (August 2017) - Barnes, Rachel D.; Barber, Jessica A.
Abstract: Motivational interviewing (MI) treatment for weight loss is being studied in primary care. The effect of such interventions on metabolic syndrome or binge eating disorder (BED), both highly related to excess weight, has not been examined in primary care. This study conducted secondary analyses from a randomized controlled trial to test the impact of MI for weight loss in primary care on metabolic syndrome. 74 adult participants with overweight/obesity recruited through primary care were randomized to 12 weeks of either MI, an attentional control, or usual care. Participants completed measurements for metabolic syndrome at pre- and post-treatment. There were no statistically significant differences in metabolic syndrome rates at pre-, X 2 (2) = 0.16, p  = 0.921, or post-, X 2 (2) = 0.852, p  = 0.653 treatment. The rates in metabolic syndrome, however, decreased for MI (10.2%) and attentional control (13.8%) participants, but not for usual care. At baseline, metabolic syndrome rates did not differ significantly between participants with BED or without BED across treatments. At post-treatment, participants with BED were significantly more likely to meet criteria for metabolic syndrome than participants without BED, X 2 (1) = 5.145, p  = 0.023, phi = 0.273. Across treatments, metabolic syndrome remitted for almost a quarter of participants without BED (23.1%) but for 0% of those with BED. These preliminary results are based on a small sample and should be interpreted with caution, but they are the first to suggest that relatively low intensity MI weight loss interventions in primary care may decrease metabolic syndrome rates but not for individuals with BED. Highlights: Study assessed impact of motivational interviewing in primary care on metabolic syndrome. Little is known about the role binge eating disorder (BED) may play. Rates of metabolic syndrome decreased in interventional groups but not usual care. Weight loss was related to improvements in metabolic syndrome diagnoses. BED diagnosis was related to new metabolic syndrome diagnoses at post-treatment.